2011
DOI: 10.2147/cpt.s16504
|View full text |Cite
|
Sign up to set email alerts
|

Chronomodulated press-coated pulsatile therapeutic system for aceclofenac: optimization of factors influencing drug release and lag time

Abstract: Background:The objective of this study was to develop and evaluate a press-coated pulsatile drug delivery system intended for treatment of early morning stiffness and symptomatic relief from pain in patients with rheumatoid arthritis. Methods: The formulation involved press coating of a rupturable coat around a rapidly d isintegrating core tablet of aceclofenac. A three-factor, two-level, full factorial design was used to i nvestigate the influence of amount of glyceryl behenate, amount of sodium chloride in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The two dotted reference lines represent the experimental variance ( Figure 3 A,C,E,G). The probability of each active effect is represented graphically as box plots and coefficients of Bayesian analysis were also calculated ( Figure 3 B,D,F,H) [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…The two dotted reference lines represent the experimental variance ( Figure 3 A,C,E,G). The probability of each active effect is represented graphically as box plots and coefficients of Bayesian analysis were also calculated ( Figure 3 B,D,F,H) [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…The low magnitudes of the bias values indicated a reasonable agreement between the predicted and the experimental values. It also indicated the robustness and high degree of predictive power of the generated quantitative mathematical models [21][22][23] . From the results obtained, it could be concluded that the generated Eqns.…”
Section: Table 5: All Responses Y1 To Y3 Along With Percent Error Formentioning
confidence: 88%
“…Arthritis Pain in the morning and more pain in the night NSAIDS, glucocorticoids [59,60] Diabetes mellitus Increase in blood sugar level after meal Sulfonyl urea, insulin, bioguanide [61].…”
Section: Transdermal Devicementioning
confidence: 99%